Effect of Solid-state Fermentation by Yeast on the Structural and Functional Properties of Wheat Bran Proteins - Tingting SHI; Yujie LU; Jiawei PEI; Runfang GUO (Shipin gongye ke-ji)
In order to investigate the possibility of solid-state fermentation of wheat bran by yeast for the production of alternative proteins, two fermented proteins were prepared in this study using wheat bran as a substrate through single and mixed bacterial fermentation. The structural and functional characteristics of the two types of fermented proteins were compared to those of wheat bran protein using sodium dodecyl sulfate-polyacrylamide (SDS-PAGE) gel electrophoresis, fourier transform infrared spectroscopy, thermogravimetric analysis, and assessment of protein processing properties and bioavailability. The results showed that the contents of total protein and soluble protein from single bacterial fermentation (DJ) and mixed bacterial fermentation (HJ) increased by 112.5%, 109.1%, 216.9%, and 449.6%, respectively, compared with those of the original wheat bran (MF). Compared with MF, the structure of DJ and HJ proteins underwent significant changes, with the proportion of β-sheet decreased significantly, while β-turn increased significantly. In addition, small molecule proteins or polypeptides <10 kDa were produced after fermentation and showed good thermal stability. The solubility and emulsifying capacity of the DJ and HJ proteins were significantly enhanced, whereas their surface hydrophobicity and foaming properties were significantly reduced. Furthermore, DJ and HJ proteins showed characteristics similar to the simulated gastrointestinal digestion as MF, with complete amino acid varieties, and the ratio of total essential amino acid to total amino acid content (EAA/TAA) increased, which was closer to the ideal pattern than MF (E/T>0.4). In summary, good functional properties and nutritional value were possessed by both single and mixed bacteria fermented proteins, which were of great significance for the production of microbial substitute proteins using wheat bran and for the development of fermented protein.